Radiative recombination through EL2 centers in selenium and cadmium single crystals doped gallium arsenide - Litvinova, M.B.; Shutov, S.V.; Shtan`ko, A.D.; Kurak, V.V. (Functional Materials, 2006)
Influence of Cd and Se atoms on the quantum efficiency of photon emission through EL2 defects in gallium arsenide single crystals has been investigated. A comparative technique of impurity diffusion in vacuum and arsenic atmospheres has been used. The change character and extent of the photon emission quantum efficiency have been established to be defined by vacancy structure of crystal that is due most likely to formation of EL2-dopant complexes.